Tacit Choice of Law in the Metaverse: What Law Applies? - Meliala, Aurora Jillena; Putra, Akbar Kurnia (Faculty of Law, Universitas Jambi, 2024)
This research discusses the reality of the metaverse with emphasis placed on the need for a rule of law for certain activities within it that is related to Private International Law. This research observes what the metaverse is, its prevalent structure and the recent dialectics on the place of international law as a comprehensive and much needed legal regime within its system. This article utilises a normative legal research methodology and uses qualitative data such as legal theories and related research to arrives at a certain conclusion on the place of Private International Law in the Metaverse. The first part of this research elaborates on the relationship between the Metaverse and Law and the importance of a clear rule of law in the Metaverse. The second part provides an overview of Private International Law in regards to the notions that exist within it to determine a prescriptive jurisdiction. The third section discusses tacit choice of law as an alternative answer to the current uncertainty in the commercial world of the Metaverse. While the last part talks about the incorporation of metaverse regulations in the domestic and regional scenes. The article finds that the need for a clear legal framework not only in regards to choice of law but also for all aspects of the Metaverse is direly needed. While tacit choice can provide legal certainty in the world of commercial contracts, a comprehensive cybersecurity regime is needed for a Metaverse that is truly based in rule of law.